Sex Bias in Experimental Immune-Mediated, Drug-Induced Liver Injury in BALB/c Mice: Suggested Roles for Tregs, Estrogen, and IL-6 - Cho, Joonhee (Public Library of Science, 2013)
BACKGROUND AND AIMS: Immune-mediated, drug-induced liver injury (DILI) triggered by drug haptens is more prevalent in women than in men. However, mechanisms responsible for this sex bias are not clear. Immune regulation by CD4+CD25+FoxP3+ regulatory T-cells (Tregs) and 17β-estradiol is crucial in the pathogenesis of sex bias in cancer and autoimmunity. Therefore, we investigated their role in a mouse model of immune-mediated DILI. METHODS: To model DILI, we immunized BALB/c, BALB/cBy, IL-6–deficient, and castrated BALB/c mice with trifluoroacetyl chloride-haptenated liver proteins. We then measured degree of hepatitis, cytokines, antibodies, and Treg and splenocyte function. RESULTS: BALB/c females developed more severe hepatitis (p<0.01) and produced more pro-inflammatory hepatic cytokines and antibodies (p<0.05) than did males. Castrated males developed more severe hepatitis than did intact males (p<0.001) and females (p<0.05). Splenocytes cultured from female mice exhibited fewer Tregs (p<0.01) and higher IL-1β (p<0.01) and IL-6 (p<0.05) than did those from males. However, Treg function did not differ by sex, as evidenced by absence of sex bias in programmed death receptor-1 and responses to IL-6, anti-IL-10, anti-CD3, and anti-CD28. Diminished hepatitis in IL-6-deficient, anti-IL-6 receptor α-treated, ovariectomized, or male mice; undetectable IL-6 levels in splenocyte supernatants from ovariectomized and male mice; elevated splenic IL-6 and serum estrogen levels in castrated male mice, and IL-6 induction by 17β-estradiol in splenocytes from naïve female mice (p<0.05) suggested that 17β-estradiol may enhance sex bias through IL-6 induction, which subsequently discourages Treg survival. Treg transfer from naïve female mice to those with DILI reduced hepatitis severity and hepatic IL-6. CONCLUSIONS: 17β-estradiol and IL-6 may act synergistically to promote sex bias in experimental DILI by reducing Tregs. Modulating Treg numbers may provide a therapeutic approach to DILI.